FAKTOR-FAKTOR YANG MEMPENGARUHI STATUS KESEHATAN MASYARAKAT PESISIR DI DALAM KEPEMILIKAN JAMBAN SEHAT - Susilawati Susilawati; Chindy Ingraini (ZAHRA: JOURNAL OF HEALTH AND MEDICAL RESEARCH, 2023)
Healthy latrines are latrines that meet building criteria and health requirements. The health requirements in question are not causing the spread of materials that are harmful to humans due to the disposal of human waste and can prevent carrier vectors from spreading disease to users and the surrounding environment. This research method is Systematic Review. by collecting literature sources from scientific journals or scientific papers published in the last five years and using electronic databases such as: Open Science Framework/OSF, Medline/Pubmed, Google Scholar and Google Scholar. The purpose of this literature study is to find out what factors influence the health status of coastal communities in owning healthy latrines. Based on the results and discussion, the education level of the people in coastal areas is mostly low, namely at the elementary-junior high school education level, which can lead to a lack of public knowledge about healthy latrines. At the income level there is a relationship between opinion and ownership of healthy latrines, in which the income of coastal communities is still lacking, low income and income that is still below the UMR, at the level of knowledge more knowledge is not good and towards attitudes there is a relationship between attitudes and ownership healthy latrines. The conclusion is that there is a relationship between education level, income, knowledge and attitudes towards owning healthy latrines  which  can  affect  the  health  status  of  coastal communities